Investigation of electrical c haracteristics of heteroepitaxial structures as a function of microrelief and manufacturing technology features - Dmitruk, N.L.; Karimov, A.V.; Konakova, R.V.; Kudryk, Ya.Ya.; Sachenko, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Over a wide temperature range (77…400 K), we studied I-V curves of photoelectric converter (solar cell) prototypes made on the basis of p-AlxGa₁-xAs– p-GaAs–n-GaAs–n⁺-GaAs heteroepitaxial structures grown on smooth or microrelief n⁺-GaAs substrates using the standard liquid phase epitaxy (LPE) and the capillary LPE from a confined volume, as well as the effect of some external factors (thermal treatment and 60Со γ-irradiation) on the current flow mechanisms. At temperatures ≤ 200 K, the tunnel component of the forward current was predominant in all the smooth samples studied up to the voltages close to 1 V, while at room temperatures all three components (diffusion, recombination and tunnel) were of the same order. This is evidenced, in particular, by the dependencys of the effective ideality factor on the applied voltage. Predominance of the tunnel current component in a wide temperature range at small biases was observed for all the solar cells obtained on the textured n⁺-GaAs substrates. In this case, an additional factor favoring the increase of the tunnel current component was relief irregularities with small curvature radii.